2005
DOI: 10.1016/s1607-551x(09)70287-6
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Study of a Health‐Promoting Lifestyle Among Southeast Asian Women in Taiwan

Abstract: The purpose of this study was to determine and understand the predicting factors of a health-promoting lifestyle (HPL) in Southeast Asian women in Taiwan. One hundred and five Southeast Asian women in Tainan were recruited. Face-to-face interviews with structured questionnaires were used for data collection. The findings showed that, among the six dimensions of HPL, subjects scored highest in self-actualization and lowest in health responsibility. Subjects who could read and write Chinese had a more positive H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
20
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 14 publications
8
20
1
Order By: Relevance
“…In addition, women’s health affects the health status of other family members. Due to sociocultural factors, health-promoting lifestyles among women have been shown to be different between countries [12]. At the individual level, personal, social, economic, and environmental factors have been found to be related to a person’s health status and health-promoting lifestyle condition.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, women’s health affects the health status of other family members. Due to sociocultural factors, health-promoting lifestyles among women have been shown to be different between countries [12]. At the individual level, personal, social, economic, and environmental factors have been found to be related to a person’s health status and health-promoting lifestyle condition.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, both caregivers and non‐caregivers scored lowest on the physical activity behavior, a result which is commonly reported among other healthy female populations in both Europe and Asia, such as Jordanian women (Ma’aitah et al. 1999), African‐American women (Johnson 2005) and Taiwanese women (Lee & Wang 2005). Combined with the results of this study, this may reflect a global trend in which women do not prioritize physical activity in their lifestyles.…”
Section: Discussionmentioning
confidence: 65%
“…Pender (1996) suggested that health‐promoting behaviors incorporate health responsibility, physical activity, nutrition, spiritual growth, interpersonal relations, and stress management. While studying different cultural groups, many researchers have used these behaviors as indicators of health‐promoting lifestyle (e.g., Drayton‐Brooks & White 2004, Lee & Loke 2005, Lee & Wang 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In spite of a desirable level of health-promoting behaviors in spiritual growth and interpersonal relationship dimensions among this group, their level of health-promoting behaviors in physical activity and health responsibility dimensions was undesirable (Enjezab et al, 2012). Lee & Wang (2005), in assessing health-promoting lifestyle among Southeast Asian women in Taiwan, showed that women had a moderate level of health-promoting behaviors and the highest score of participants was in the spiritual growth dimension and the lowest score was in the level of physical activity. Chen et al reported that the average overall Health Promotion Lifestyle Profile score of postpartum Taiwanese women was low (mean: 2.83; SD: 1.35), with exercise rated lowest among the six subscales (Chen, Kuo, Chou, & Chen, 2007).…”
Section: Introductionmentioning
confidence: 99%